Real-Time Monitoring of Glutathione in Living Cells Reveals that High Glutathione Levels Are Required to Maintain Stem Cell Function - Eui Man Jeong; Ji-Hye Yoon; Jisun Lim; Ji-Woong Shin; A. Young Cho; Jinbeom Heo; Ki Baek Lee; Jin-Haeng Lee; Won Jong Lee; Hyo-Jun Kim; Young Hoon Son; Seok-Jin Lee; et al. (Stem Cell Reports, 2018)
Summary: The core functions of stem cells (SCs) are critically regulated by their cellular redox status. Glutathione is the most abundant non-protein thiol functioning as an antioxidant and a redox regulator. However, an investigation into the relationship between glutathione-mediated redox capacity and SC activities is hindered by lack of probe. Here, we demonstrate that cyanoacrylamide-based coumarin derivatives are ratiometric probes suitable for the real-time monitoring of glutathione levels in living SCs. These probes revealed that glutathione levels are heterogeneous among subcellular organelles and among individual cells and show dynamic changes and heterogeneity in repopulating SCs depending on oxidative stress or culture conditions. Importantly, a subpopulation of SCs with high glutathione levels exhibited increased stemness and migration activities in vitro and showed improved therapeutic efficiency in treating asthma. Our results indicate that high glutathione levels are required for maintaining SC functions, and monitoring glutathione dynamics and heterogeneity can advance our understanding of the cellular responses to oxidative stress. : By developing and characterizing new fluorescent probes enabling fast, reversible, and ratiometric reaction with glutathione, Jeong et al. reveal considerable dynamics and heterogeneity in glutathione levels in living stem cells in response to environmental stress and also show that high glutathione levels are required for maintaining stemness of murine embryonic stem cells or therapeutic potency of mesenchymal stem cells. Keywords: glutathione, fluorescent probe, real-time monitoring, stem cell, oxidative stress, heterogeneity, pluripotency, self-renewal, migration, asthma